Design and development of continuous pineapple-peeling machine - Jiraporn Sripinyowanich Jongyingcharoen; Ekkapong Cheevitsopon; A Ahanbakhshi; Y Abbaspour-Gilandeh; T Gundoshmian; A Anjali; P Anjitha; K Neethu; A Arunkrishnan; P Vahid; S Mathew; Z Arsad; et al. (Agriculture and Natural Resources, 2022)
A continuous pineapple peeler was designed having a mechanism to align the pineapple during peeling for use in small to medium-sized enterprises. Objectives: To design, fabricate and test the performance of a continuous pineapple peeler based on the physical and mechanical properties of pineapples.
Keywords: Pineapple and bromelain studies